Medication guide for dose adjustment and management of cardiotoxicity and lipid metabolic adverse events of oral antineoplastic therapy - Ramos-Ruperez, Elena; Escudero-Vilaplana, Vicente; Ruiz-Briones, Paula; Collado-Borrell, Roberto; Villanueva-Bueno, Cristina; Revuelta-Herrero, José Luis; González-Haba, Eva; Garcia-Gonzalez, Xandra; Ibañez-Garcia, Sara; Perez-Ramirez, Sara; Zatarain-Nicolás, Eduardo; Herranz, Ana; et al. (Frontiers in Oncology, 2023)
Objective The management of cardiotoxicity is a challenge for healthcare professionals concerning the use of oral antineoplastic agents (OAAs). Our objective was to create a comprehensive medication management guide with dose adjustment recommendations on OAAs concerning cardiotoxic and lipid metabolic adverse events (AEs) to assist healthcare professionals when prescribing these drugs. Material and Methods A review of the available information on all dose adjustments necessary to prescribe and dispense OAAs safely concerning cardiotoxicity was conducted. In January 2023, we identified all OAAs authorized by the European Medicines Agency (EMA). For each drug, the latest summary of product characteristics (SPC) approved by the EMA and the tertiary data source Lexicomp® were reviewed. Cardiotoxic AEs were recorded: QT interval prolongation, decrease in left ventricular ejection fraction (LVEF), imbalances in blood pressure (hypertension and hypotension), alterations in heart rate (tachycardia and bradycardia), and thrombosis. Any available dose adjustment recommendations in case of occurrence of these adverse events were collected. Results Ninety-three different OAAs had been approved by the EMA and were reviewed. Amongst them, 51.6% have recognized cardiotoxic AEs and 10.8% of them can cause alterations in lipid metabolism. A total of 27 (29.0%) OAAs had specific recommendations about QT prolongation; 88.9% were listed in the SPC and 59.3% in Lexicomp®. Eight OAAs (9.68%) have reported a decrease in LVEF, and four of these drugs have specific management recommendations: encorafenib, lorlatinib, ripretinib, and sunitinib. Almost half (49.5%) of currently approved OAAs can potentially alter blood pressure; 34 (36.6%) of them have been reported to cause hypertension, and 12 (12.9%) are related to hypotension. Tachycardia and/or bradycardia are associated with 22.6% and 8.6% of the evaluated drugs respectively. Regarding thrombosis, 30 (32.3%) of the drugs analyzed included the appearance of thrombus as a possible AE. Conclusions More than half of the OAA can produce cardiotoxic effects, the most frequent are blood pressure alteration and QT interval prolongation with a non-depreciable incidence of LV dysfunction or thrombosis. Before starting the treatment, it is necessary to stratify baseline cardiovascular risk, to plan a surveillance schedule, and to consider referral to cardio-oncology units.